Privacy and RFID Technology: A Review of Regulatory Efforts. Issue 2 (13th January 2017) - Turri, Anna M.; Smith, Ronn J.; Kopp, Steven W.
Abstract : Radio Frequency Identification (RFID) is rapidly becoming a common tool for manufacturers and retailers as they seek to manage supply chains and provide products and services to consumers. However, the widespread use of RFID technology also introduces consumer privacy concerns. This article reviews current regulatory efforts related to RFID, identifies gaps, calls for the enforcement of current guidelines, and provides suggestions for future research.